Response of Add-On Oral Levetiracetam in Neonates Having Refractory Seizure (Medical Forum Monthly, 2024)
Objective: To evaluate the efficacy of add on oral levetiracetam in neonates having refractory seizure.Study Design: A prospective clinical trialPlace and Duration of the Study: This study was conducted at the Department of Pediatrics, Services Hospital, Lahore from June 2018 to March 2019.Materials and Methods: We analyzed 60 neonates visiting neonatal emergency with seizure, who did not respond to initial intravenous (IV) phenobarbital or subsequent addition of IV phenytoin. We went on to use oral levetiracetam as an add on therapy. Oral levetiracetam as gavage as a starting dose of 10 to 20 mg per kg and gradual increase to 40 to 50 mg per kg if a repeat of seizure occurred according to clinical signs and then, persistence or complete control of seizure was monitored. Chi square test was applied to the effect of study variables on the response of levetiracetam and p value < 0.05 was considered as statistically significant.Results: Out of a total of 60 neonates, most were 40 (66.7%) male, had gestational age status as term 38 (43.3%), delivered by cesarean section (CS) 39 (65.0%), aged less than or equal to 7 days 42 (70.0%). Tonic seizure was found to be the most frequent type, in 19 (31.7%) while 18 (30.0%) had idiopathic as the commonest underlying cause of seizure. There were 56 (93.3%) neonates who went on to positively respond to add on therapy of oral levetiracetam.Conclusion: Oral levetiracetam as an add on therapy was found to have excellent response in neonate having seizure after the failure of 1st line treatment options.